Non-invasive quantitative assessment of oxidative metabolism in quadriceps muscles by near infrared spectroscopy - Ding, H.; Wang, G.; Lei, W.; Wang, R.; Huang, L.; Xia, Q.; Wu, J. (British Journal of Sports Medicine, 2001)
BACKGROUND:Near infrared spectroscopy can be used in non-invasive monitoring of changes in skeletal muscle oxygenation in exercising subjects. OBJECTIVE:To evaluate whether this method can be used to assess metabolic capacity of muscles. Two distinctive variables abstracted from a curve of changes in muscle oxygenation were assessed. METHODS:Exercise on a cycle ergometer was performed by 18 elite male athletes and eight healthy young men. A measuring probe was placed on the skin of the quadriceps muscle to measure reflected light at two wavelengths (760 and 850 nm), so that the relative index of muscle oxygenation could be calculated. Exercise intensity was increased from 50 W in 50 W increments until the subject was exhausted. During exercise, changes in muscle oxygenation and blood lactate concentration were recorded. The following two variables for assessment of muscle oxygenation were then abstracted and analysed by plotting curves of changes in muscle oxygenation: the rate of recovery of muscle oxygen saturation (R(R)) and the relative value of the effective decrease in muscle oxygenation (D(eff)). RESULTS:Data analysis showed a correlation between muscle oxygenation and blood lactate concentration at the various exercise intensities and verified the feasibility of the experiment. Data for the athletes were compared with those for the controls using the Aspin-Welch test of significance; t = 2.3 and 2.86 for R(R) and D(eff) respectively. There were significant differences (p = 0.05) between the athletes and the control group with respect to these two variables. CONCLUSION:R(R) and D(eff) may be distinctive variables that can be used to characterise muscle oxidative metabolism during human body movement.